Nature of the evidence base and frameworks underpinning dietary recommendations for prevention of non-communicable diseases: a position paper from the Academy of Nutrition Sciences. Issue 7 (14th October 2021) - Williams, Christine M.; Ashwell, Margaret; Prentice, Ann; Hickson, Mary; Stanner, Sara
Abstract: This Position Paper from the Academy of Nutrition Sciences is the first in a series which describe the nature of the scientific evidence and frameworks that underpin nutrition recommendations for health. This first paper focuses on evidence which underpins dietary recommendations for prevention of non-communicable diseases. It considers methodological advances made in nutritional epidemiology and frameworks used by expert groups to support objective, rigorous and transparent translation of the evidence into dietary recommendations. The flexibility of these processes allows updating of recommendations as new evidence becomes available. For CVD and some cancers, the paper has highlighted the long-term consistency of a number of recommendations. The innate challenges in this complex area of science include those relating to dietary assessment, misreporting and the confounding of dietary associations due to changes in exposures over time. A large body of experimental data is available that has the potential to support epidemiological findings, but many of the studies have not been designed to allow their extrapolation to dietary recommendations for humans. Systematic criteria that would allow objective selection of these data based on rigour and relevance to human nutrition would significantly add to the translational value of this area of nutrition science. The Academy makes three recommendations: (i) the development of methodologies and criteria for selection of relevant experimental data, (ii) further development of innovative approaches for measuring human dietary intake and reducing confounding in long-term cohort studies and (iii) retention of national nutrition surveillance programmes needed for extrapolating global research findings to UK populations. Abstract :